2015
DOI: 10.1111/jtxs.12110
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Attitudes Toward Texture and Other Food Attributes

Abstract: This study aims to examine the current attitudes of North American consumers toward food attributes, focusing on the effect of gender and age. A total of 337 participants were asked to list the first three words that come to mind when each image/name of 32 different foods was presented. The responses were grouped into seven main categories: “food attribute,” “menu uses,” “type,” “personal preference,” “health and nutrition,” “regional origin” and “others” and subsequent subcategories. The frequencies of answer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 31 publications
0
26
3
1
Order By: Relevance
“…Our study clearly shows that depending on the food, a texture may be accepted or rejected. For instance, crunchy and crispy, for a US population, are among the most liked textures (Luckett & Seo, 2015). However, they are also leading causes of rejection when present in certain foods like onions.…”
Section: Discussionmentioning
confidence: 99%
“…Our study clearly shows that depending on the food, a texture may be accepted or rejected. For instance, crunchy and crispy, for a US population, are among the most liked textures (Luckett & Seo, 2015). However, they are also leading causes of rejection when present in certain foods like onions.…”
Section: Discussionmentioning
confidence: 99%
“…Szczesniak () found that texture is taken for granted and consumers do not comment on it unless texture is off or inappropriate (Szczesniak, ). Food texture is a discernible attribute, and in some foods (meat, apples, and potato), it may be more important than flavor (Hogenkamp, Stafleu, Mars, Brunstrom, & de Graaf, ; Luckett & Seo, ; Nicklaus, Demonteil, & Tournier, ; Szczesniak, ). Previous research indicated overall consumer acceptability of pork was first related to tenderness, followed by flavor intensity and then by juiciness (Moeller et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Szczesniak (2002) found that texture is taken for granted and consumers do not comment on it unless texture is off or inappropriate (Szczesniak, 2002). Food texture is a discernible attribute, and in some foods (meat, apples, and potato), it may be more important than flavor (Hogenkamp, Stafleu, Mars, Brunstrom, & de Graaf, 2011;Luckett & Seo, 2015;Nicklaus, Demonteil, & Tournier, 2015;Szczesniak, 1971).…”
Section: Understanding Consumer Terminologymentioning
confidence: 99%
“…Healthy individuals have a predominantly positive disposition toward eating foods and commercial food products were likely to evoke pleasant emotions (Desmet & Schifferstein, ). Luckett and Seo () stated that most respondents chose the “like” subcategory to indicate personal preference for the food sample. These might lead to a hedonic asymmetry tendency for some products.…”
Section: Resultsmentioning
confidence: 99%